Pengaruh Kepemilikan Manajerial dan Ukuran Perusahaan terhadap Kualitas Laba dengan Konservatisme Akuntansi sebagai Variabel Moderasi: Studi pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2019-2022 - Ade Putera Kristiadi; Sri Yuni; Christina Fransiska (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The goal of this research is to determine how management ownership and business size affect profits quality while also taking into consideration the moderating effect of accounting conservatism. Companies making food and drink products that are included in the IDX population from 2019 to 2022. As part of the sample procedure, twenty-four companies were chosen at random. Data analysis is performed using SPSS version 25. In this research, we employ a variety of statistical tests, including the t-test and the coefficient of determination, in addition to descriptive statistics, tests of classical assumptions, multiple regression analysis, and moderated regression analysis, to determine whether or not hypotheses hold. The tests’ results show that the firm’s size has a far more significant impact on profit quality than does management ownership. Therefore, where there is management ownership, conservatism as a moderator has no influence on the quality of earnings. However, accounting conservatism may weaken the link between company size and profit quality.